Cutis marmorata telangiectatica congenita. Report of 4 cases. - Barba, A.; Tessari, G.; Molesini, M.; Schena, D. (European Journal of Pediatric Dermatology, 1997)
Four cases of cutis marmorata telangiectatica congenita (CMTC) observed in the period September 1994-May 1995 are reported. The first patient (G.D.) presented a rare clinical variant of CMTC, which is called cross dimelic form. In the case here reported the right upper limb and the left lower limb were affected. Moreover, he presented patent foramen ovale and ectasic distal tract of the left ureter. Only two cases of the cross dimelic form have been so far reported in the relevant literature. All four patients spontaneously improved with time and exhibited normal physical and mental development. The observation of four cases in a 9-month period of time led the Authors to believe that CMTC is more frequent than what reported in the literature. Probably, the less severe forms from a clinical point of view are underdiagnosed. A close relationship between pediatricians and dermatologists could result in a precocious diagnosis of CMTC and also of the malformations which can be associated with CMTC.